2009
DOI: 10.1021/jp905054d
|View full text |Cite
|
Sign up to set email alerts
|

Liquid−Liquid Phase Separation in Mixed Organic/Inorganic Aerosol Particles

Abstract: Currently, the physical state of mixed organic/inorganic aerosol particles is not well characterized, largely because of the still unclear chemical composition of the organic fraction and of its properties with respect to mixing with the inorganic fraction. To obtain insight in the possible phases and phase transitions of such aerosol particles, we investigated the ternary poly(ethylene glycol)-400/ammonium sulfate/water system as a representative model system with partially immiscible constituents. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
336
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(373 citation statements)
references
References 49 publications
27
336
4
Order By: Relevance
“…The schlieren developed into small droplets that coalesced to form an inner phase within the particle. Ciobanu et al (2009) have also observed spinodal decomposition for LLPS of PEG-400/AS/H 2 O particles. At 71.9 % RH, inner and outer phases together with satellite inclusions can be clearly discriminated in the liquid droplet.…”
Section: Llps Features Of C5/as/h 2 O C6/as/h 2 O and C7/as/h 2 O Drmentioning
confidence: 72%
See 4 more Smart Citations
“…The schlieren developed into small droplets that coalesced to form an inner phase within the particle. Ciobanu et al (2009) have also observed spinodal decomposition for LLPS of PEG-400/AS/H 2 O particles. At 71.9 % RH, inner and outer phases together with satellite inclusions can be clearly discriminated in the liquid droplet.…”
Section: Llps Features Of C5/as/h 2 O C6/as/h 2 O and C7/as/h 2 O Drmentioning
confidence: 72%
“…The most prominent feature in the reference spectrum of crystalline AS is the symmetric stretching vibration of SO 2− 4 at ∼975 cm −1 (Zhang and Chan, 2002;Ling and Chan, 2008;Ciobanu et al, 2009). The band of the stretching vibration of NH + 4 at around 3130 cm −1 (Ciobanu et al, 2009;Yeung et al, 2009) is also distinguished. The C6 and C7 references reveal C-H stretching vibrations at 2880-2984 and 2875-2990 cm −1 , respectively, and several peaks between 700 and 1670 cm −1 .…”
Section: Chemical Compositions Of the Different Phasesmentioning
confidence: 97%
See 3 more Smart Citations